Comparison of continuous dynamics probing with the standard penetration test for highly weathered limestone of eastern Sudan - Mohammed Ahmed, Omar Babiker Elhaj (2010)
Insitu soil tests in general have the advantage of allowing measurements under the field environmental conditions with minimum amount of soil disturbance due to sampling. A comparison of continuous dynamic probing with the SPT has been made for a case study of highly weathered limestone in Eastern Sudan. The correlation of Modified Light Dynamic Penetrometer, DPLmod with the Standard Penetration Test, SPT is obtained in terms of penetration resistance. Two types of correlation are obtained using statistical analysis: DPN300 vs. SPTN300 and DPN100 vs. SPTN300. The analysis results have indicated a general trend line of linear correlation without intercept. The obtained correlations were compared to some previous similar correlations. This comparison indicated that this study produced correlations that have the same trend line as that for the previous studies. The correlations of this research are found to be better than the similar correlations collected from the literature review as reflected by the correlation coefficient, which is ranging from 0.85 to 0.92 for the current research correlations and from 0.31 to 0.89 for the previous correlations. This comparison supports the idea of this research and is considered as a successful step for producing correlations for this simple method. The relationship between input energy and theoretical energy for both continuous dynamic probing and standard penetration test as well as the relationship between input energies for both types of tests was produced. It is found that the Engineering News Record (ENR) formula is the most suitable to represent the SPT theoretical energy, whereas for the dynamic probing theoretical energy the formula after Gates (1957) is the best one. This study has verified high degree of consistency between the two tests.